the vertical asymptote and horizontal asymptote
![\begin{gathered} f(x)=(x^2-1)/(x^2+3x+2) \\ f(x)=((x-1)(x+1))/((x+1)(x+2)) \\ f(x)=(x-1)/(x+2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/v7gvimrkgr1bci46qpmmqv3571ho17ujbm.png)
The vertical asymptote is x+2 = 0, x = -2
The horizontal asymptote is x - 1 = 0, x = 1
the x-intercept and the y-intercept
The intercept with x is calculated as 0 f(x)
![\begin{gathered} f(x)=0 \\ (x-1)/(x+2)=0 \\ (x-1)=0 \\ x=1 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/37o16enrjo3ar44at29z79zrz5h22un9tr.png)
The intercept with x is (1,0)
The intercept with y is calculated for x = 0
![\begin{gathered} f(0) \\ (x-1)/(x+2) \\ (0-1)/(0+2) \\ (-1)/(2) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gt1mj426weesye2isv27bccy785hyabvk3.png)
The intercept with y is (0,-1/2)